A prospective study of the patterns and dynamics of colonization with Candida spp. in very low birth weight neonates. (November 2013) - Leibovitz, Eugene; Livshiz-Riven, Ilana; Borer, Abraham; Taraboulos-Klein, Tali; Zamir, Orly; Shany, Eilon; Melamed, Rimma; Rimon, Orna-Flidel; Bradenstein, Rita; Chodick, Gabriel; Golan, Agneta
Abstract Background: Knowledge of fungal colonization patterns in very low birth weight infants (VLBWI) admitted to the neonatal intensive care unit (NICU) is essential in understanding the process of fungal infections in neonates. We analyzed prospectively, during 2009–2010, the patterns and dynamics of fungal colonization in VLBWI, including timing, colonization sites, and species involved. Methods: Weekly skin, oropharynx, and rectum/stool surveillance fungal cultures were collected from admission until discharge in VLBWI in the NICU. None received antifungal prophylaxis. Results: Overall, 118 VLBWI provided 1723 samples; 34 (29%) had 104 positive samples at least once during the first 10 hospitalization weeks. Thirty-nine (33%) weighed < 1000 g; 68 were delivered by cesarean section. Candida albicans (57/104, 55%) and Candida parapsilosis (26/104, 25%) were the main fungi isolated. Eight (24%) VLBWI were colonized during the first week and 23 (68%) during the second week. No differences in colonization were recorded between cesarean section and vaginally delivered VLBWI. The colonization risk at least once during the first 10 weeks was 23% for skin, 14% for oropharynx, 27% for rectum/stool, and 38% for any anatomic site sampled. Persistent colonization was recorded in 5/34 (15%), while transient colonization was found in 14/34 (41%) VLBWI; 16/34 (47%) were discharged or died colonized with Candida spp. Candidemia was diagnosed in 4 (3%) VLBWI and previous/simultaneous colonization was found in 3/4. Conclusions: The cumulative risk of colonization, at any sampled site and at least once during follow-up, was high. Initial colonization occurred most often during the first 2 weeks of life. Colonization dynamics were characterized by various persistence, disappearance, and recolonization patterns. Candidemia was rare.